The Influence of Entrepreneurial Education and Managerial Skills toward the Productivity of Silk Industry in Wajo Regency - Manrapi, Ramli; Tawe, Amiruddin; Haerani, Haerani; Hisyam, Hisyam (International Review of Management and Marketing, 2017)
South Sulawesi province constitutes the province in which produces silk and becomes one of the center of Silk industries in Indonesia i.e. Wajo Regency. In addition to make a living from agricultural crops, the people there are as well skillful and competent at weaving the silk fabric in general. Silk weaving activities can be easily seen and found in several districts in Wajo, South Sulawesi, Indonesia. Wajonese people have been long well known with their entrepreneur spirit and skills which are shown and proven by the ability to create the silk fabric from the very manual, traditional and conventional weaving tools and instruments called non machinery weaving instruments (ATBM). In spite of the rise of tough competition and penetration from other silk producers either of domestic or foreign ones. In domestic area, Sumatera and Aceh offer their traditional fabric i.e. Songket fabric. Meanwhile, India and Thailand are as well taking part in the competition by offering high quality silk and silk fabric as a result of the opening of ASEAN Economic Community (AEC) begun eelier this year i.e. 2016 which is indicated by 5 things i.e. the free flow of goods, service, investment, educated workforce and capital so as to demand the Indonesian people in general and the business doers or entrepreneur either in small, medium and big scale in particular to master the science and technology which are based on the ability and skills either in production field or in the managerial ones oriented in entrepreneurial culture. Keywords: entrepreneurial education, managerial ability, industrial performance JEL Classification: L6